Sustainable Human Resource Management Impact on Work Engagement, Employability, and Job Satisfaction at An Indonesian State-Owned Construction Company - Cahyadi, Lukman; Raka, Resha Resnandi; Utami, Vince Lorenza (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
Sustainable human resource management on employee intrinsic motivation manifests in work engagement, employability, and job satisfaction. This research uses a quantitative-deductive method because it has a clear and measurable population and sample. This research employs the purposive sampling method with permanent employees of an Indonesian state-owned construction company in the construction sector in Indonesia as the respondents. Structured equation model – partial least squares (SEM PLS) is used in processing and analyzing the data obtained. The research results explain the strong influence of SHRM on work engagement, employability, and job satisfaction. This research contributes academically to provide a new perspective for company management to apply the concept of sustainability in human resource management. The findings from this research can be used by policymakers to develop policies for SHRM in their organization. The application of the sustainability concept to human resource management allows companies to gain opportunities to achieve performance from a financial, social, and ecological perspective in the long term.